(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Based on data of infectious disease 9,72 percent teenagers in institute of special development (LPKA) had a history of COVID-19 disease, 4,17 percent had a history of Tuberculosis, and 1,39 percent had a history of COVID-19 and Tuberculosis. Also found that 5,4 percent teenagers in institute of special development (LPKA) are malnourished, and 5,4 percent overnourished. According to WHO, the factors that affected of nutrition status are direct factors such as food intake and infectious diseases, and indirect factors is knowledge. To get an optimal nutrition status, teenagers are recommended to apply Balanced Nutrition Guidelines which is visualization through Isi Piringku. This research aims to find out differences of knowledge and eating behaviour before and after education of Isi Piringku with animation power-point media in teenagers for one weeks research by one times of education and two times of reinforcement. The research design is one group pr and post-test design with a sample of 43 teenagers aged 14-18 years old in institute of special development for children (LPKA) class one of Tangerang taken by simple random sampling with the lottery method. After being analyzed with the Wilcoxon test there was a significant increase in knowledge (p=0,000), the average pre-test score was 48,32 to 76,35 on the post test. The eating behaviour of Isi Piringku has increased in sufficient category by 32,5 percent. Also showed decreased of intake occurred in animal side dishes significantly (p=0,021).